Does Septic Tank Revitalisation Impact the Triple Burden of Malnutrition in Toddlers? - Wenny Arta Simamora; Khoirunurrofik Khoirunurrofik (PT. Publikasiku Academic Solution, 2025)
The triple burden of malnutrition (TBM) is the coexistence of overnutrition, undernutrition, and micronutrient deficiencies in a population. TBM leads to future chronic health problems, high healthcare costs, and challenges to sustainable development. One of the factors that contributes to TBM is environmental conditions. The Provincial Government of DKI Jakarta, in an effort to fulfill the community's right to a healthy environment, has been implementing a septic tank revitalization subsidy program from 2020 to 2022. This study aims to investigate the impact of the Septic Tank Revitalization Subsidy program on the Triple Burden of Malnutrition among under-fives in policy-affected households and identify other factors that are important in influencing the reduction in the prevalence of Triple Burden of Malnutrition. Using the Difference-in-Differences method with data on households receiving the Septic Tank Revitalization Subsidy program through the DKI Jakarta Provincial Water Resources Office and the results of the One Stop Family Data Collection survey in two waves of data collection obtained through the DKI Jakarta Provincial Empowerment, Child Protection and Population Control Office, this study concludes that the septic tank revitalization subsidy policy has not significantly influenced the reduction of the Triple Burden of Malnutrition in children under five years old. Other factors that are found to be important and significantly influential are the history of worms, drinking water sources, grandmultipara, and participation of children under five in integrated health service post (posyandu).